Polymer Physics : Applications to Molecular Association and Thermoreversible Gelation - Tanaka, F. (Fumihiko), 1947- (Cambridge ; New York : Cambridge University Press, 2011)
"The field of polymer science has advanced and expanded considerably in recent years, encompassing broader ranges of materials and applications. In this book, Fumihiko Tanaka unifies the subject matter, pulling together research to provide an updated and systematic presentation of polymer association and thermoreversible gelation, one of the most rapidly developing areas in polymer science. Starting with a clear exposition of the fundamental laws of polymer physics, subsequent chapters discuss a new theoretical model that combines thermodynamic and rheological theory. Recent developments in polymer physics are explored, along with important case studies on topics such as self-assembly, supramolecules, thermoreversible gels and water-soluble polymers. Throughout the book, a balance is maintained between theoretical descriptions and practical applications, helping the reader to understand complex physical phenomena and their relevance in industry. This book has wide interdisciplinary appeal and is aimed at students and researchers in physics, chemistry and materials science"--
Machine generated contents note: Preface; 1. Statistical properties of polymer chains; 2. Polymer solutions; 3. Classical theory of gelation; 4. Rubber elasticity; 5. Associating polymer solutions; 6. Nongelling associating polymers; 7. Thermoreversible gelation; 8. Structure of polymer networks; 9. Rheology of thermoreversible gels; 10. Some important thermoreversible gels; Index.
Includes bibliographical references and index.
Keywords: Polymers; Gelation; Polymer colloids; TECHNOLOGY & ENGINEERING / Chemical & Biochemical